Предмет: Математика,
автор: defender234734
Помогите решить пожалуйста
Приложения:
Ответы
Автор ответа:
0
а)y' = 2x +4
б) y' = -6/x² +1/√ч
в) y'= ((x⁶ -4x +1)'*x - (x⁶ -4x+1)*x')/x² =((6x⁵-4)*x -x⁶+4x-1)/x²=
=(6x⁶-4x-x⁶+4x-1)/x² = (5x⁶-1)/x²
г) y'=1
д) y'=((3x-4)'*(7-2x) - (3x -4)*(7-2x)')/(7-2x)²=
=(3(7-2x)+2(3x-4))/(7-2x)²= (21-6x +6x -8)/(7-2x)²=13/(7-2x)²
e) y'=6Cos2x
ж) y'=1/2√(x²-4x) * (x²-4x)' = (2x-4)/2√(x²-4x)=(x-2)/√(x²-4x)
б) y' = -6/x² +1/√ч
в) y'= ((x⁶ -4x +1)'*x - (x⁶ -4x+1)*x')/x² =((6x⁵-4)*x -x⁶+4x-1)/x²=
=(6x⁶-4x-x⁶+4x-1)/x² = (5x⁶-1)/x²
г) y'=1
д) y'=((3x-4)'*(7-2x) - (3x -4)*(7-2x)')/(7-2x)²=
=(3(7-2x)+2(3x-4))/(7-2x)²= (21-6x +6x -8)/(7-2x)²=13/(7-2x)²
e) y'=6Cos2x
ж) y'=1/2√(x²-4x) * (x²-4x)' = (2x-4)/2√(x²-4x)=(x-2)/√(x²-4x)
Похожие вопросы
Предмет: История,
автор: iskravika2005
Предмет: Геометрия,
автор: Аноним
Предмет: Математика,
автор: alex70586080
Предмет: Физика,
автор: Бердник